Utilization of Sugar Palm (Arenga pinnata) Dreg in Biodegradable Plastic Processing - Yudi Pranoto; Budi Ariyani Hermawati; Wahyu Supartono; Agung Putra Pamungkas (Indonesian Food and Nutrition Progress, 2022)
Bioplastics are made from biomass sources that can be decomposed naturally in a relatively short time compared to plastics produced from synthetic polymers plastic. Sugar palm dregs are a promising source for bioplastics due to their abundance and renewability, and they do not compete with human needs. Sugar palm dregs contain enough crude fiber (41.66%) to produce strong bioplastics. Chitosan and glycerol are added to improve the performance of bioplastics. The responses observed included tensile strength, elongation at break, young modulus, thickness, biodegradability, and water vapor permeability. This study aims to determine the factors’ effect on the response parameters and find the optimal multiresponse combination to fabricate sugar palm dreg-based bioplastics. The experimental design was determined using Taguchi method, and multiresponse analysis was carried out using the Grey Relational Analysis approach. The results show that adding sugar palm dreg increased the tensile strength, Young modulus, and thickness of bioplastics but decreased the elongation at break. Adding chitosan affected the water vapor permeability, and glycerol increased the biodegradation percentage of bioplastics. The optimal combination of sugar palm dreg bioplastic was 3 grams of sugar palm dreg, 2 grams of chitosan, and 3 grams of glycerol. The combination resulted in a tensile strength of 1.46 MPa, 24.49 of elongation at break, 6.08 MPa of young modulus, 0.28 mm of thickness, 100% of biodegradation, and 0.61 g.mm/kPa.hour.m2. The results show that sugar palm dreg bioplastic is potential as future food packaging.